(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
A series of novel sulfonated poly(arylene ether sulfone) (SPAES) were prepared by aromatic nucleophilic substitution polycondensation from 4, 4'-dichlorodiphenylsulfone (DCDPS), 3, 3'-disulfonated-4, 4'- dichlorodiphenylsulfone (SDCDPS) and 4-fluorophenyl hydroquinone and characterized by viscosity measurement, FT-IR, ^1H-NMR and TG. The SPAES membranes consisting of different ratio of SDCDPS to DCDPS were cast from their solutions. The alternating current (AC) proton conductivity of SPAES membranes were carried on. The values of inherent viscosity ranging from 1.04 to 2.43 dl/g, implying that SPAESs possessed high molecular weight. The results of TG analysis showed SPAESs were thermal stable up to nearly 200 °C. The acid forms (H^+) of SPAES films were tough and ductile with the tensile strength of 61-91 Mpa. The proton conductivity of SPAES films became higher with the increasing content of SDCDPS in chain composition. SPAES with 50% SDCDPS showed the highest proton conductivity of 0.205 S/cm at 80 °C. The water uptake and dimension swelling of SPAES membranes were also measured. At the same time, SPAES showed excellent proton transportation stability when used at high temperature. SPAESs had a higher water uptake than Nafion 115, while experimental IEC of SPAESs in the range of 0.77-1.35 meq/g at 80 °C were very closed to the calculated ones.